Medicinal Properties of Pomegranate - Esfandiar Hassani Moghadam *; Mahdi Shaaban; Asghar Sepahvand (Lorestan University of Medical Sciences, 2020)
As an ancient fruit tree, pomegranate (Punica granatum L.) is one of the unique fruit trees cultivated in the Mediterranean region, particularly in Iran and in the Middle East. This tree is cultivated in majority of Iranian provinces. The mineral content and medicinal properties of pomegranate have been indicated in many previous research reports. The present review focuses on the medicinal properties of pomegranate fruit. Based on previous researches, we concluded that pomegranate has several medicinal uses in human diet. All parts of pomegranate tree have medicinal uses. Anti-cancer property is the main medicinal characteristic of this fruit tree. Pomegranate fruit has high amounts of phenolic compounds with a remarkable antioxidant activity. Moreover, one of the principal phenolic ingredients of pomegranate is ellagic acid which is characterized by high antioxidant activity. This review focuses on the recent researches on the medicinal properties of pomegranate fruit. The antioxidant activities and medicinal properties of pomegranate that are effective in the treatment of certain diseases were identified. However, we collected the best results of previous studies in carried out on this subject.